2004
DOI: 10.1111/j.1444-0903.2004.00515.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of selective cyclooxygenase‐2 inhibitors on anti‐ulcer medication and non‐steroidal anti‐inflammatory drug use in patients with rheumatic disease

Abstract: Among rheumatology patients, selective COX-2 inhibitors have largely replaced NSAIDs and have resulted in a reduction in AUM consumption, but prescribing patterns for selective COX-2 inhibitors have not been related clearly to risk factors for GI complications. The introduction of selective COX-2 inhibitors has been associated with a significant increase in expenditure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…We stand by the conclusions in our paper 1 (editorialized in the same issue of Internal Medicine Journal ) 2 . The study was conducted in a clinical setting and although the economic analysis was of limited scope, we feel that the results are relevant to the understanding of the costs and benefits arising from everyday prescribing practice.…”
mentioning
confidence: 86%
“…We stand by the conclusions in our paper 1 (editorialized in the same issue of Internal Medicine Journal ) 2 . The study was conducted in a clinical setting and although the economic analysis was of limited scope, we feel that the results are relevant to the understanding of the costs and benefits arising from everyday prescribing practice.…”
mentioning
confidence: 86%
“… † Note that Joshua et al . 1 reported on p. 154 that the ‘pre‐release’ data were sampled in 1998, but this statement was referenced to a 1993 study (query whether this is a referencing error or a typo); ‡ Taken or derived from Joshua et al. Table 6, p. 159; § Taken or derived from Joshua et al.…”
Section: Relative Contribution Of Nsaid Coxib and Anti‐ulcer Medicatmentioning
confidence: 99%
“…The cost‐benefit analysis by Joshua et al . showed that the net cost of ‘the introduction of COX‐2 inhibitors’ was $71 736 per serious GI hospital admission prevented (p. 153) 1 . We wish to stress that this limited (author's words) cost‐benefit analysis should not be confused as a cost‐effectiveness analysis of Coxibs.…”
Section: Cost‐effectiveness Datamentioning
confidence: 99%
See 1 more Smart Citation
“…In this month's issue of the Internal Medicine Journal , Joshua et al. analyse the patterns of use of the highly selective cyclooxygenase (COX)‐2 inhibitors during the first 16 months of their release into the Australian market, and attempt a partial assessment of their costs and benefits 1 . The COX‐2 inhibitors were of course developed in the hope that the human and financial costs of non‐steroidal anti‐inflammatory drug (NSAID)‐induced ulcers would be reduced, but also in the reali­sation that the drug costs of NSAID treatment would be bound to increase − at least while the new drugs have patent protection.…”
mentioning
confidence: 99%